Changes in Total Physical Activity, Leisure and Commuting in the Largest City in Latin America, 2003-2015 - De Moraes-Ferrari, G (NLM (Medline), 2021)
OBJECTIVE: To analyze the prevalence of physical inactivity and the average time of practice of total physical activity and by domains (leisure and commuting), according to gender, age group and schooling, between 2003 and 2015, in residents of the urban area of the city of São Paulo. METHODS: Data from Household Health Surveys in the Municipality of São Paulo (2003: n = 2,514; 2015: n = 4,043). The International Physical Activity Questionnaire was used to measure total, leisure, and commuting physical activity. Results were presented in < 10 minute/week periods, physical inactivity and minutes/week, according to evaluation period, sex, age and schooling. RESULTS: Prevalence of < 10 minutes/week periods in 2003 and 2015 were: 22.5 and 28.9% for the total; 56.7 and 58.3% for leisure; and 35.2 and 39.9% for commuting, with significant change only in the total item, among adolescents (10.3 to 18.8%). For physical inactivity, prevalence rates were: 54.9 and 61.6% (total); 78.2 and 78.9% (leisure); and 72 and 79.9% (commuting), with significant changes only for commuting among adults (67.8 to 77.4%). For the average in minutes per week, in total, there was a significant decrease for female adolescents (138.2 minute/week) and adults with 0-8 (122.6 minutes/week) and 9-11 years (96.7 minutes/week) years of schooling; in commuting, there was a reduction for female adolescents (95 minutes/week); and male adults (95 minutes/week) and female adults (82 minutes/week). CONCLUSIONS: There were no reductions in the prevalence of < 10 min/week periods or leisure physical inactivity. Commuting physical inactivity has become even more common.